2015
DOI: 10.1016/j.pmn.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor and Urinary Distress in Women with Fibromyalgia

Abstract: Fibromyalgia (FM) patients were recently found to have more symptom burden from bothersome pelvic pain syndromes that women seeking care for pelvic floor disease at a urogynecology clinic. We sought to further characterize pelvic floor symptoms in a larger sample of FM patients using of validated questionnaires. Female listserv members of the Fibromyalgia Information Foundation completed an online survey of three validated questionnaires: the Pelvic Floor Distress Inventory 20 , the Pelvic Pain, Urgency and Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
1
19
1
1
Order By: Relevance
“…This could be possibly attributed to the fact that FIQR was collected via online blogs in women with greater level of awareness concerning their disease. Moreover, the significant positive correlation between FIQR and PFDI‐20 and PFIQ‐7 scores confirmed the previous findings reported by Jones et al This is an interesting outcome that highlights the significant additional impact caused by PFD symptoms on the overall burden experienced by patients with fibromyalgia.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This could be possibly attributed to the fact that FIQR was collected via online blogs in women with greater level of awareness concerning their disease. Moreover, the significant positive correlation between FIQR and PFDI‐20 and PFIQ‐7 scores confirmed the previous findings reported by Jones et al This is an interesting outcome that highlights the significant additional impact caused by PFD symptoms on the overall burden experienced by patients with fibromyalgia.…”
Section: Discussionsupporting
confidence: 88%
“…The level of distress caused by PFD was significantly more pronounced in patients with fibromyalgia compared to the control group as shown by the PFDI‐20 outcome scores. In the study conducted by Jones et al, the total PFDI‐20 score in 177 patients with fibromyalgia was slightly higher (159 ± 55) than the total scores reported by our sample of patients with fibromyalgia (143 ± 5.7), with the greatest contribution to the total distress originating from the colorectal‐anal symptoms followed by genital prolapse and urinary symptoms . In another study, patients with genital prolapse symptomatology who self‐reported fibromyalgia scored a total of 145 ± 63 on the PFDI‐20 and 105 ± 84 on the PFIQ‐7 which were significantly higher compared to subjects reporting genital prolapse symptoms but not fibromyalgia .…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations